The relationship between blood pressure and sciatic nerve blood flow velocity in rats with insulin-treated experimental diabetes. (July 2014) - Olver, T Dylan; Grisé, Kenneth N; McDonald, Matthew W; Dey, Adwitia; Allen, Matti D; Rice, Charles L; Lacefield, James C; Melling, CW James; Noble, Earl G; Shoemaker, J Kevin
Peripheral nerve blood flow (NBF) does not autoregulate but, instead, responds passively to changes in mean arterial pressure (MAP). How this relationship is impacted by insulin-treated experimental diabetes (ITED) is unknown. We tested the hypothesis that ITED will reduce NBF across a range of MAP in Sprague Dawley rats. Following 10 weeks of control or ITED conditions, conscious MAP (tail-cuff) was measured, and under anaesthesia, the MAP (carotid artery catheter, pressure transducer) and NBF (Doppler ultrasound, 40 MHz) responses to sodium nitroprusside (60 µg/kg) and phenylephrine (12 µg/kg) infusion were recorded (regression equations for MAP vs NBF were created for each rodent). Thereafter, motor nerve conduction velocity (MNCV) and nerve vascularization (haematoxylin and eosin stain) were determined. Conscious MAP was higher and MNCV was lower in the ITED group ( p < 0.01). In response to drug infusions, the ΔMAP and ΔNBF were similar between groups ( p ≥ 0.18). Estimated conscious NBF (based on substituting conscious MAP values into each individual regression equation) was greater in the ITED group ( p < 0.01). Sciatic nerve vascularization was similar between groups ( p ≥ 0.50). In contrast to the hypothesis, NBF was not reduced across a range of MAP. In spite of increased estimated conscious NBF values, MNCV was reduced in rats with ITED.